2006
DOI: 10.1093/nar/gkl1032
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of microRNA target gene expression reveals that miRNA targets are lower expressed in mature mouse and Drosophila tissues than in the embryos

Abstract: MicroRNAs (miRNAs) are non-coding small RNAs of ∼22 nt that regulate the gene expression by base pairing with target mRNAs, leading to mRNA cleavage or translational repression. It is currently estimated that miRNAs account for ∼1% of predicted genes in higher eukaryotic genomes and that up to 30% of genes might be regulated by miRNAs. However, only very few miRNAs have been functionally characterized and the general functions of miRNAs are not globally studied. In this study, we systematically analyzed the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 61 publications
8
83
0
1
Order By: Relevance
“…The short length of the seed sequence facilitates the targeting of many transcripts by a single miRNA (3). Some estimates suggest that 30% of all eukaryotic genes are regulated by miRNAs (4,5). miR-155, a miRNA widely reported to be involved in lymphoma, is also now emerging to have a role in the progression of solid cancers (6).…”
mentioning
confidence: 99%
“…The short length of the seed sequence facilitates the targeting of many transcripts by a single miRNA (3). Some estimates suggest that 30% of all eukaryotic genes are regulated by miRNAs (4,5). miR-155, a miRNA widely reported to be involved in lymphoma, is also now emerging to have a role in the progression of solid cancers (6).…”
mentioning
confidence: 99%
“…Currently, it is estimated that up to 30% of protein coding genes might be regulated by miRNAs at the posttranscriptional level. 4,5 Recent studies have demonstrated that miRNAs regulate various cell functions, including cell proliferation, differentiation, death, stress resistance, and fat metabolism. 4 -6 Accordingly, it is reasonable to suggest that abnormal miRNAs expression is likely to contribute to human disease, including cancer.…”
mentioning
confidence: 99%
“…They found that the expression levels of miRNA targets are significantly lower in all mouse mature tissues and Drosophila later life stages than in the embryos. These results point out that miRNAs may play roles in determining the timing of tissue differentiation during the larva period of Drosophila development and maintaining the tissue identity during adulthood [66].…”
Section: Contribution To Maintain Tissue Identitymentioning
confidence: 69%